Genome-Wide Variation in Potyviruses - Nigam, Deepti; LaTourrette, Katherine; Souza, Pedro F. N.; Garcia-Ruiz, Hernan (Frontiers in Plant Science, 2019)
Potyviruses (family Potyviridae, genus Potyvirus) are the result of an initial radiation event that occurred 6,600 years ago, and currently consist of 167 species that infect monocots or dicots, including domesticated and wild plants. Potyviruses are transmitted in a non-persistent way by more than 200 species of aphids. As indicated by their wide host range, word-wide distribution, and diversity of their vectors, potyviruses have an outstanding capacity to adapt to new hosts and environments. Factors that confer adaptability are poorly understood. Viral RNA-dependent RNA polymerases introduce nucleotide substitutions that generate genetic diversity. We hypothesized that selection imposed by hosts and vectors creates a footprint in areas of the genome involved in host adaptation. Here, we profiled genomic and polyprotein variation in all species in the genus Potyvirus. Results showed that the potyviral genome is under strong negative selection. Accordingly, the genome and polyprotein sequence are remarkably stable. However, nucleotide and amino acid substitutions across the potyviral genome are not randomly distributed and are not determined by codon usage. Instead, substitutions preferentially accumulate in hypervariable areas at homologous locations across potyviruses. At a frequency that is higher than that of the rest of the genome, hypervariable areas accumulate non-synonymous nucleotide substitutions and sites under positive selection. Our results show, for the first time, that there is correlation between host range and the frequency of sites under positive selection. Hypervariable areas map to the N terminal part of protein P1, N and C terminal parts of helper component proteinase (HC-Pro), the C terminal part of protein P3, VPg, the C terminal part of NIb (RNA-dependent RNA polymerase), and the N terminal part of the coat protein (CP). Additionally, a hypervariable area at the NIb-CP junction showed that there is variability in the sequence of the NIa protease cleavage sites. Structural alignment showed that the hypervariable area in the CP maps to the N terminal flexible loop and includes the motif required for aphid transmission. Collectively, results described here show that potyviruses contain fixed hypervariable areas in key parts of the genome which provide mutational robustness and are potentially involved in host adaptation.